Guarda-roupa encantado: espetacularidade das roupas de caboca do terreiro estandarte de Rei Sebastião, Outeiro - Pará - CASTRO, Otávia Feio (Universidade Federal do Pará, 2017)
Grounded in Ethnoscenology in its transdisciplinary perspective, this research sought to understand the spectacular of the clothes used by Mariinha Jesus Costa Feio, mother-of-saint and caretaker Terreiro Sebastian King Banner, located in Outeiro Island, in Pará. The clothes are dressed in days that celebrates the cabocas entities of the tambor of mina, Herondina and Maria Légua - boss and counter-boss of mother-of-saint respectively - and belonging to a enchanted category mining pantheon - as Luca (2010) the enchanted are described as those who have not had the experience of death and did address in encantarias: forests, rivers, and other environments. To understand these clothes and full experience with the studied phenomenon, thanks to the assumptions of ethnographic research Geertz (2014); the experience period in terreiro realized from june 2015 to may 2016, in which experienced two parties: the caboca Herondina in august and caboca Maria Légua in december. This research aims to contribute to the Etnocenológicos studies in the Amazon, in view of the strength and tradition of the Tambor of Mina in Pará. Noteworthy is also important for those who work with clothes in a general context and more specifically to the costume designers, because during reflections and writing this essay, I took the authorial proposition of costume-etnocenológica, you need constantly exercise the ontological look - in the sense developed by Paes Loureiro (2008). Exercise this that helped to understand the spectacular character of these clothes, which for its making meet previously organized specifics, highlighting what the mother-of-saint of this place says about their cabocas and myths related to Dona Herondina and Dona Maria Légua.